Variability in triage practices for critically ill cancer patients: A randomized controlled trial (2019)
Purpose: Intensive care triage practices and end-user interpretation of triage guidelines have rarely been assessed. We evaluated agreement between providers on the prioritization of patients for ICU admission using different triage guidelines. Materials and methods: A multi-centered randomized study on providers from 18 different countries was conducted using clinical vignettes of oncological patients. The level of agreement between providers was measured using two different guidelines, with one being cancer specific. Results: Amongst 257 providers, 52.5% randomly received the Society of Critical Care Prioritization Model, and 47.5% received a cancer specific flowchart as a guide. In the Prioritization Model arm the average entropy was 1.193, versus 1.153 in the flowchart arm (P = .095) indicating similarly poor agreement. The Fleiss' kappa coefficients were estimated to be 0.2136 for the SCCMPM arm and 0.2457 for the flowchart arm, also similarly implying poor agreement. Conclusions: The low agreement amongst practitioners on the prioritization of cancer patient cases for ICU admission existed using both general triage guidelines and guidelines tailored only to cancer patients. The lack of consensus on intensive care unit triage practices in the oncological population exposes a potential barrier to appropriate resource allocation that needs to be addressed. © 2019 Elsevier Inc.